A Descriptive Analysis of Macronutrient, Fatty Acid Profile, and Some Immunomodulatory Nutrients in Standard and Disease-Specific Enteral Formulae in Europe - Ruperto, Mar; Montero-Bravo, Ana; Partearroyo, Teresa; Puga, Ana M.; Varela-Moreiras, Gregorio; Samaniego-Vaesken, Maria de Lourdes (Frontiers in Nutrition, 2022)
Food for special medical purposes (FSMP) are commercially available formulations used as a source of nutrition when administered orally or by tube feeding. This study examines for the first time, the nutritional composition of enteral formulae (EFs) according to European nutritional guidelines. We developed a descriptive study in 118 EFs from 2020-2021. Formulae were classified as standard (SF) and disease specific (DSF). SFs were classified according to protein-energy content into: G1, Normoprotein-normocaloric; G2, Normoprotein-hypercaloric; G3, Hyperproteic-normocaloric and G4, Hyperproteic-hypercaloric. Disease related formulae for metabolic stress, renal, cancer, pulmonary, diabetes, malabsorption and surgery were studied. Macronutrient distribution, fatty acid profile [monounsaturated (MUFA), polyunsaturated (PUFA), and saturated (SFA)], derived fat quality indexes, and immuno-modulatory nutrients [omega-3, eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), arginine and nucleotides] per 1500 kcal infused were calculated. Fifty-three percent were SFs, mainly normoproteic (G1, G2) with higher carbohydrate contents in normocaloric vs. hypercaloric SFs. Most balanced fatty acid profile (MUFA:17.7%; PUFA:6.8%; SFA:9.5%) belonged to G1. The PUFA/MUFA-ratio: ≥0.5 was in 85.7% with higher proportion of EPA+DHA (46%) vs. omega-3 (15.8%) in SFs. In DSFs (46.9%), higher carbohydrate content (>50%), was in malabsorption and surgery, whereas high fat content (>50%) was in pulmonary and renal formulae. DSFs had higher SFA vs. MUFA content, except for diabetes. EPA and DHA was added in 45.5% (cancer, malabsorption, and surgery). Only 12.7% of DSFs had arginine and nucleotides. A higher proportion of SFs were found, in line with current European guidelines. Results highlighted a wide intra-group variability of nutrients among the formula selected. These findings are useful to evaluate the nutritional composition of EFs from a preventive and/or therapeutic perspective in clinical settings.